1933 Or. Laws 488, ch. 315, § 2 - (:unkn) unknown (My University, 1933)
Prohibited a unnaturalized person and person convicted of a felony against another person or the government from owning or possessing a pistol, revolver, other firearm, or machine gun. Punishable by imprisonment for 1-5 years.
Keywords: POSSESSION - DANGEROUS PERSONS